Specific Exercises and their Effect on the Anaerobic Speed Reserve and Run Achievement 400 M for Young People - Naeem Ajeel, Ali; Mohammad Kadhim, Saif (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study was to prepare specific training exercises for 400 m youth, as well as the effect of qualitative training in the anaerobic speed reserve for the 400 m running efficiency of youth, while there were statistically significant differences between the pre- and post-tests to 400 m running for the youth. The researcher followed the experimental approach in the design of one group with the prel and post tests, which is compatible with the nature of the problem and its objectives. The study was conducted on a randomly selected sample of the antagonists of Wasit Governorate for the 400 m class of young people. The number of (6) was selected out of (9) divided into three clubs. The researcher then conducted a homogeneity between them. The researcher applied his training curriculum for 8 weeks and 3 training modules within the main section of the session and in the preparation period for them. The specific exercises included exercises of explosive nature, quick strength, speed, and endurance speed during the training units. The researcher took care of the age and grade of the group. The duration of the application of the training method was carried out by the researcher to conduct posttests, in light of which data was obtained using the appropriate statistical means, which showed the evolution of both variables (anaerobic speed reserve and completion of the 400 m run) and for the benefit of posttests. To the need to pay attention to the use of qualitative exercises and the inclusion of exercises for the anaerobic speed reserve for events requiring speed and strength.